Ligand-free one-step synthesis of 001 faceted semiconducting BiOCl single crystals and their photocatalytic activity - Biswas, Anupam; Das, Raja; Dey, Chandan; Banerjee, Rahul; Poddar, Panka (Crystal Growth & Design, 2014)
Herein, we report one-step ligand-free hydrothermal synthesis of predominantly {001}-faceted micron-sized single crystals of bismuth oxychloride (BiOCl). The structural chlorine is obtained by in situ generation of chloride ions. From Raman spectra, we could resolve the E-g transition. Photocatalytic activity of as-synthesized crystals showed 78% degradation of RhB dye under a xenon source after 120 min of exposure.